Study of Wind Turbine based SEIG under Balanced/Unbalanced Loads and Excitation - Ashwani Kumar Sharma; A. Kumar; K. S. Sandhu (Institute of Advanced Engineering and Science, 2012)
This paper presents the performance of a stand-alone self-excited induction generator (SEIG) driven by fixed pitch wind turbine. The main objective of the paper is: (i) dynamic study of SEIG under balanced R-L/R-C loads (ii) dynamic study of SEIG under balanced and unbalanced excitation, (iii) Fixed pitch wind turbine model has been considered for driving induction generator. An approach based on dynamic equations of an isolated SEIG under balanced/unbalanced conditions of loads is employed to study the behaviour of the system. The SEIG model with balanced/un-balanced load and excitation has been simulated using MATLAB/SIMULINK.DOI:http://dx.doi.org/10.11591/ijece.v2i3.303